Heterogeneous catalytic ozonation: The significant contribution of PZC value and wettability of the catalysts. Issue 5 (October 2021) - Psaltou, Savvina; Kaprara, Efthimia; Triantafyllidis, Konstantinos; Mitrakas, Manassis; Zouboulis, Anastasios
Abstract: The aim of this study is to evaluate the role of PZC and wettability of the catalysts in heterogeneous catalytic ozonation process. For that purpose, 18 solid materials examined as potential catalysts for heterogeneous catalytic ozonation, regarding the degradation of small amounts (4 μΜ) of p-chlorobenzoic acid ( p -CBA - typical micropollutant) at pH 7. The examined catalysts belong to three main categories, i.e., metal oxides/hydroxides, minerals, and carbons. Alumina 507, SiO2, Bayoxide, zeolite, calcite and dolomite were found to be the optimum catalysts with p -CBA removal rates higher than 99.4% after the 3rd min of the process. The obtained results indicate the importance of surface charge and the wettability degree of the catalysts. It was found that the affinity between ozone and the catalyst surface and the subsequent production of hydroxyl radicals ( OH) depends on these parameters. More specifically catalysts of high wettability and neutrally to slightly positive surface charged led to enhanced p -CBA degradation. The strongly negative or positive surface charged materials that present low wettability were found to decrease the OH production. Although, in the gas phase ozone presents better affinity with the non-polar/hydrophobic surfaces, when it is dissolved in water and participates in aqueous phase oxidation reactions, the contact with the catalysts' surface is enhanced by the higher wettability of the solids, promoting the production of OH. In addition to the activation of ozone on the catalysts' surface, it was shown that their efficiency is enhanced by the initial p -CBA adsorption on the surface of applied catalysts. Graphical Abstract: ga1 Highlights: PZC value determines the affinity of ozone with a solids' surface. Neutral to slight positive surface charge enhance OH production. Wettability improves the contact of dissolved O3 with the active centers of catalyst surface. Dissolved O3 has better affinity with the hydrophilic surfaces than the hydrophobic O3 gas. Micropollutant adsorption contributes to heterogeneous catalytic efficiency.